The Moral Experience of the Patient with Chronic Pain: Bridging the Gap Between First and Third Person Ethics. Issue 3 (5th December 2013) - Edwards, Ian; Jones, Mark; Thacker, Michael; Swisher, Laura Lee
Abstract Background There has been a widespread call for an ethics in the management of patients with chronic pain which is patient centered and takes into account the lived experience of the patient. It has been argued in literature that current "duty" or principlist‐based models of ethics (so‐called 3rd person ethics) have not adequately addressed the needs of either patients or practitioners in this area. Method Two strands of literature within phenomenology were reviewed: the literature of interpretative phenomenological analysis and the study of the lived experience of the person with chronic pain; and the contribution of phenomenology in neo‐Aristotelian virtue ethics (1st person ethics). Findings Patients experience chronic pain in existential and moral terms in addition to their biomedical issues, facing dilemmas in understanding their own self‐identity and in attempting to recover a sense of moral worth and agency. Discussion We outline a patient‐centered ethics to underpin contemporary collaborative, multimodal approaches in the management of chronic pain. We firstly describe an agency‐oriented, neo‐Aristotelian 1st person ethics and then outline a hermeneutic relationship with extant "duty‐based, " 3rd person bioethics. The utility of the ethics model we propose (the ethical reasoning bridge) lies in its capacity for developing a sense of moral agency for both practitioner and patient, resonating with the current emphasis of seeking active engagement of patients in management.